Yeast Particles for Encapsulation of Terpenes and Essential Oils - Ernesto R. Soto; Florentina Rus; Zeynep Mirza; Gary R. Ostroff (Molecules, 2023)
Terpenes and essential oils are materials of great commercial use due to their broad spectra of antibacterial, antifungal, membrane permeation enhancement and antioxidant biological properties, as well as for their use as flavors and fragrances. Yeast particles (YPs) are 3–5 µm hollow and porous microspheres, a byproduct of some food-grade yeast (Saccharomyces cerevisiae) extract manufacturing processes, that have been used for the encapsulation of terpenes and essential oils with high payload loading capacity (up to 500% weight) and efficiency, providing stability and sustained-release properties. This review focuses on encapsulation approaches for the preparation of YP–terpene and essential oil materials that have a wide range of potential agricultural, food and pharmaceutical applications.